Integration of Ergo-Manufacturing and Simulation to Minimise Waiting Time for Cracker and Kemplang Production Process Flow (Case Study of PT. Belimo Food Industry) - Setiawan, Heri; Susanto, Sani; Rinamurti, Micheline; Alfian, Achmad (Ann Publisher, 2025)
Belimo Food Industry factory is engaged in the production of crackers and kemplang with the Belimo brand. Observations made at the packing workstation, there is still a buildup or bottleneck in the press machine that is not optimal and performance is not efficient because it violates many ergonomic principles in the manufacturing industry (Ergo-Manufacturing). This research explores the integration of Ergo-Manufacturing concepts with simulation. The research aims to improve performance and reduce process lead time. The research method used is quantitative-descriptive with primary data. Data processing uses the integration method of the Ergo-Manufacturing concept with Arena software-based simulation so as to provide solutions that can optimise the performance of process waiting time, improve efficiency, work comfort, and production capacity at the packing workstation. The results of the study after applying Ergo-Manufacturing with work environment settings can minimise the waiting time of the initial condition process with a process time of 58.273 minutes. Under the conditions of improvement scenario 1, the process waiting time of 26,830 minutes can reduce the process time by 60%, under the conditions of improvement scenario 2, the process waiting time of 14,562 minutes can reduce the process waiting time by 80% and under the conditions of improvement scenario 3, the process waiting time of 12,483 minutes can reduce the process time by 85%. The results of the BEP decision analysis for scenario 1 were selected by adding 1 press machine to 2 press machines which can increase production capacity by 128 products and reduce overtime costs incurred by the company for 1.5 hours by IDR 40,500 and BEP investment in press machines takes 3 years.